Peningkatan Kompetensi Guru Dalam Perencanaan Pembelajaran Tematik Melalui Supervisi Kelompok Pendekatan Kolaboratif - Rukayah, Rukayah (Universitas Kristen Satya Wacana, 2018)
This research was conducted with the aims to improve the competence of developing thematic learning plans in improving the quality of thematic learning in class I, II, and III in primary school Ungaran 05. Subjek research in this action research is a low-grade teacher at SD Negeri Ungaran 05. The school action researcher was conducted in two cycles, with the stages of planning, acting, observing and reflecting in each cycle. The collected data is analyzed quantitatively and qualitatively. The results of school action research concluded that group supervision with collaborative approach can improve the competence of lower class teachers in Elementary School Ungaran 05 in preparing thematic lesson planning.